(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In French linguistics, like in all languages, the use of euphemism has been formed as a historical ethnographic phenomenon in connection with the phenomenon of taboo. Euphemism is associated with the development of customs, cultural level, aesthetic taste and ethnic norms in nations. With the development of the language, its euphemistic layer also develops. Euphemism and dysphemism are contradictory concepts, if euphemism serves to hide and soften words considered to be "taboo" - "forbidden", "unpleasant", dysphemisms, on the contrary, are the rude, unpleasant words that reinforce taboo words through the use of expressions. This article deals with the concepts of "euphemism" and "taboo" in linguistics, particularly in French linguistics, as well as the concept of dysphemism, lexical-semantic relations of euphemic-dysphemic units.